Women Who Stay: A Morality Work Perspective. (25th May 2017) - Davis, Jenny L; Love, Tony P
Abstract: Women who choose to stay in abusive relationships occupy a morally ambiguous identity category. They are at once pitied for their victimhood and shamed for their participation in it. We examine debates over women who stay using the highly publicized case of Janay Rice, who actively defended her professional football player husband, Ray Rice, following the release of a video in which he knocked her unconscious. Specifically, we engage in sentiment analysis and qualitative coding of discourse on Twitter following key points in the case (N = 3, 761). We show that negative sentiment towards Ray Rice, the media, and the National Football League act as clear mechanisms of boundary reinforcement through which abusers, exploiters, and enablers of abuse are morally censured. In contrast, Janay Rice becomes the site of a boundary war. Moral detractors accuse Janay of greed, mental incapacity, and jeopardizing women's safety and empowerment. Moral defenders neutralize Janay through allusions to pure victimhood and medical disorder, and valorize Janay as courageous, empowered, and devoted to her family. These moral debates, though centering on a single incident, represent the collective negotiation of meanings around women who stay.